Investigation of causes of foaming in industrial waste water treatment and effects of substances in industrial waste water treatment - Maleka, Mamohau Julia (Vaal University of Technology, 2012)
The research was aimed to study the causes of excessive foaming in a waste water treatment plant. Although the activated sludge process has been adopted to treat this industrial waste water , lots of problems were experienced by the inhibitory effects of toxic compounds that are found in industrial effluents and the foaming stability that was very high. Industrial waste water treatment using sludge processes was found to be more challenging than the normal municipal waste water treatment although the principle is the same; the foaming tendencies were found to be more in industrial waste water. In this study the composition of influents to the waste water treatment plant and operating parameter’s effects on foaming tendencies were examined. The foaming potential in the plant was found to be chemically related due to high contamination of compounds such as phenols, which played a major role in formation of stable foam. It was recommended that there must be pretreatment of the incoming influents to minimize their impact to waste water treatment.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: Foaming; Industrial; Waste water treatment; Factory and trade waste.; Water -- Pollution.; Water -- Purification -- Foam fractionation.; Dissertations, Academics -- South Africa.